1990
DOI: 10.1111/j.1752-1688.1990.tb01349.x
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF BEST MANAGEMENT PRACTICES FOR CONTROLLING NONPOINT POLLUTION FROM SILVICULTURAL OPERATIONS1

Abstract: Fifteen years of streamflow and water quality data were evaluated to determine the effectiveness of Best Management Practices (BMP's) in controlling nonpoint source pollution from an 110. acre commercial clearcut located in the Ridge and Valley Province of central Pennsylvania. The analyses addressed both short‐ and long‐term changes in the physical and chemical properties and the hydro‐logic regime of the stream draining this 257‐acre watershed. Overall, the BMP's employed on this commercial clearcut were ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…The land cover changes following timber harvesting can cause alterations in nutrient retention and water discharge mechanisms (Dillon & Kirchner, 1975;Lynch & Corbett, 1990). Silvicultural activities are known to raise the water temperature and increase the release of nutrients and minerals from soil to streams (Campbell & Doeg, 1989;William, Taylor, Warren, & Clingenpeel, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The land cover changes following timber harvesting can cause alterations in nutrient retention and water discharge mechanisms (Dillon & Kirchner, 1975;Lynch & Corbett, 1990). Silvicultural activities are known to raise the water temperature and increase the release of nutrients and minerals from soil to streams (Campbell & Doeg, 1989;William, Taylor, Warren, & Clingenpeel, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Three sub-basins in each lake watershed were selected for clear cut harvesting to approximately 25%-40% of timber up to the buffer zone along each watercourse. Clear cutting or land cover changes can alter the nutrient retention mechanisms in soil that subsequently affect the quality of water in stream and lakes in the watershed (Lynch & Corbett, 1990;Martin & Pierce, 1980;Pomeroy, 2003). Swank, Vose, and Elliott (2001) reported that following clear cutting of mixed hardwoods on a southern Appalachian catchment the on-site impacts were soil and nutrient losses and offsite impacts were on stream water quality, attributed to the altered chemistry and flow rates, sedimentation, and impacts on invertebrate habitat and community structure.…”
mentioning
confidence: 98%
“…It will not attempt to review the large body of literature that exists on effects of forest management on water quality in uplands. For such information, see Beasley (1979), Martin et al (1984), McClurkin et al (1985), Brown (1989), Lynch and Corbett (1990), and Binkley and Brown (1993). Some of the sites discussed in this review are in the transitional zone between wetlands and uplands, and thus, there is uncertainty whether they would be classified as wetlands by various regulatory guidelines.…”
mentioning
confidence: 97%
“…NPSs did not receive significant attention until the implementation of the Federal Clean Water Act, Section 208, in 1970, which includes increased land-use regulations and encourages best-management practices (BMP) for reducing loads of contaminants, such as nitrogen and phosphorus, to streams from nonpoint sources. BMPs are practices that are determined by the State to be practical and effective in achieving and maintaining NPS loads at levels compatible with water-quality goals and may include stormwater management, headwater protection practices, or zoning restrictions on development (Lynch and Corbett, 1990).…”
Section: Relation Of Water Quality To Land Use In the Drainagementioning
confidence: 99%